Kerala's economy : crouching tiger, sacred cows - Mani, Sunil; Kochar, Anjini; Kumar, Arun M. (D.C. Books, 2006)
Papers presented at a conference held in 2005 in Thiruvananthapuram, Kerala, India; articles with reference to Kerala, India.